The short- and long-run impacts of financial crises on youth unemployment in OECD countries. Issue 34 (21st July 2017) - Bruno, Giovanni S. F.; Choudhry Tanveer, Misbah; Marelli, Enrico; Signorelli, Marcello
ABSTRACT: The impact of financial crises on the youth unemployment rate (YUR), compared to the total unemployment rate (UR), is estimated for a panel of OECD countries over the period 1981–2009, using bias-corrected dynamic panel data estimators of short- and long-run coefficients. Both YUR and UR are found highly persistent. Also, short- and long-run effects of financial crises on YUR are significantly large, respectively, some 1.9 and 1.5–1.7 times higher than the short- and long-run effects on UR. Similar results are found for the unemployment impacts of GDP growth lagged 1 year and institutional variables. These results are robust to various dynamic specifications.